Supporting Coaches' Mental Health: A Critical Review of Psychological Interventions for Depression - Abdollahi Dehkordi , Amir Mohammad; Lagunes-Carrasco, Jose Omar (Health Nexus, 2023)
The current study investigates the critical and often overlooked issue of mental health among sports coaches, with a specific focus on depression and its psychological interventions. Coaches, known for their pivotal role in guiding athletes, face unique stressors and challenges that predispose them to mental health issues, notably depression. This paper comprehensively examines the effectiveness of various psychological interventions aimed at combating depression in this specific demographic. Through a meticulous selection of studies, we analyze interventions such as Cognitive Behavioral Therapy (CBT), mindfulness techniques, peer support networks, and other therapeutic strategies. The review not only highlights the efficacy of these interventions but also compares their applicability and impact within the coaching context. By identifying gaps in the current literature and practice, the article underscores the urgent need for tailored mental health support for coaches. The insights gained from this review are intended to inform future research directions, contribute to the development of targeted mental health programs, and ultimately foster a healthier, more supportive environment in the sports coaching community. This article serves as a call to action, emphasizing the crucial role of mental health care in sustaining the well-being and performance of coaches, who are instrumental in the athletic and personal development of athletes.